Côte d’Ivoire : les aires protégées entre politique de conservation contrastée et réinterprétation sociale - Walter Kouamé Kra (Études Caribéennes)
The degradation of protected areas in Ivory Coast is analyzed in this paper from the perspective of the conflicting interests of stakeholders. In a qualitative approach based on the grounded theory, individual interviews and secondary data, the article shows the contradictions of protected areas management policy. These contradictions are opportunely reinterpreted by the illegal occupiers as a tacit premium for growing cocoa of which Côte d’Ivoire remains the first world producer. They thus highlight the whole sociality of the ecological disaster underway in the country, going beyond the thesis which attributes, in the literature, the causes of this degradation, essentially to urbanization and to existential anthropogenic pressure.